Territorial Expansion of the Ragusan Commune/Republic and the Churches of Its Patron Saints - Marinković, Ana (Array, 2009)
The churches of St Blaise and the earlier Ragusan patron saints on the territory of the Ragusan commune/Republic are analysed hagiotopographically from the oldest sources available up to the fifteenth century. Geographical distribution of the church buildings points to two major patterns of topographic expansion and the use of the patron cults in the course of Dubrovnik's transformation from commune to republic - from a defensive act of marking the borders with temples to a developed system of implanting the state cult into the administrative seats.